2015
DOI: 10.1016/j.jphys.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Taping does not decrease swelling in acute, lateral ankle sprain of athletes: a randomised trial

Abstract: Brazilian Registry of Clinical Trials, RBR-32sctf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 19 publications
1
33
0
2
Order By: Relevance
“…15 Other studies have examined the efficacy of KT application in other study variables such as muscle excitability, 21 strength, 22,23 neuromuscular control, 24 and joint swelling. 25 These studies have found limited or no benefit to support the use of KT tape, with benefit only seen in muscle excitability in the calf muscles with KT application, 21 and strength in the quadriceps. 23,26 A recent meta-analysis examining the effects of KT tape on skeletal muscle strength have found that the tape does not promote strength gains in healthy adults.…”
Section: The Effects Of Kt In a Postsurgical Musculoskeletal Populationmentioning
confidence: 99%
“…15 Other studies have examined the efficacy of KT application in other study variables such as muscle excitability, 21 strength, 22,23 neuromuscular control, 24 and joint swelling. 25 These studies have found limited or no benefit to support the use of KT tape, with benefit only seen in muscle excitability in the calf muscles with KT application, 21 and strength in the quadriceps. 23,26 A recent meta-analysis examining the effects of KT tape on skeletal muscle strength have found that the tape does not promote strength gains in healthy adults.…”
Section: The Effects Of Kt In a Postsurgical Musculoskeletal Populationmentioning
confidence: 99%
“…The tape, which is elastic, porous, and adhesive, can be applied easily to the low back region and does not restrict joint mobility during exercises [ 10 ]. Although the effects of KT in clinical studies are controversial [ 11 – 14 ], some beneficial effects of KT have been reported, such as the normalization of muscular function, the correction of possible joint misalignment [ 11 , 12 ], and enhanced neuromuscular performance [ 13 ]. Hence, we postulated that KT might be an ideal adjunct to TRX training to activate the core muscles in people with chronic LBP.…”
Section: Introductionmentioning
confidence: 99%
“…All of the SRs investigated taping strategies to treat ankle sprains [7,[76][77][78][79][80][81]. There were eight RCTs related to ankle sprains [5,[62][63][64][65][66][67][68]. The overall PEDro scores ranged from 1 to 8.…”
Section: Anklementioning
confidence: 99%